Study about Glycated Hemoglobin - A Predictor of COVID Severity - Balaji Vijayam; Madhuri S. Balaji; Taarika Balaji; Seshiah Veerasamy; A. Anitha Rani; Shalini Devaraj (Recent Developments in Medicine and Medical Research Vol. 5, 2021)
Worldwide healthcare professionals work tirelessly to treat COVID-19 infected patients. Diabetes have a negative impact on the prognosis of patients with COVID-19. Adverse outcomes can be predicted by both hyper and hypoglycemia in hospitalized patients, further it leads to chronic inflammation and multiple organ damage, which promotes oxidative stress and release of inflammatory mediators. Thus glycemic control must be optimized in diabetic patients when infected with COVID-19 to reduce their risk of disease severity. The influence of HbA1c on mortality of patients with COVID-19 and T2DM individuals remains unclear. Thus the current article focused on the association between the levels of HbA1c with the severity of COVID-19 among T2DM patients.